Casparian strips prevent apoplastic diffusion of boric acid into root steles for excess B tolerance - Muro, Keita; Kamiyo, Jio; Wang, Sheliang; Geldner, Niko; Takano, Junpei (Frontiers in Plant Science, 2023)
Casparian strips are ring-like structures consisting of lignin, sealing the apoplastic space between endodermal cells. They are thought to have important functions in controlling radial transport of nutrients and toxic elements in roots. However, Arabidopsis mutants with a defective Casparian strip structure have been found to maintain nutrient homeostasis in ranges supportive of growth under standard laboratory conditions. In this study, we investigated the function of Casparian strips under excess boron (B) conditions using sgn3 and sgn4 mutants with defective Casparian strip development but which do not exhibit excessive deposition of suberin, another endodermal diffusion barrier. The growth of sgn3 and sgn4 mutants did not differ significantly from that of wild-type (WT) plants under different B conditions in plate cultures; however, they were highly sensitive to B excess in hydroponic culture, where transpiration drives the translocation of boric acid toward the shoot. In hydroponic culture with sufficient to excess boric acid, B accumulation in shoots of the sgn3 and sgn4 mutants was higher than that in the WT. A time-course tracer study using 10 B-enriched boric acid at a sufficient or slightly excessive concentration showed higher translocation of B into shoots of the sgn3 and sgn4 mutants. Furthermore, a genetically encoded biosensor for boric acid expressed under a stele-specific promoter (proCIF2:NIP5;1 5′UTR:Eluc-PEST) visualized faster boric acid flux into the mutant steles. Collectively, our results demonstrate the importance of Casparian strips in preventing apoplastic diffusion of boric acid into the stele under excess supply.